Taeniasis and Cysticercosis as A Zoonotic Parasitic Disease - Estuningsih, Sarwitri Endah (Indonesian Animal Sciences Society, 2009)
Taeniasis is a parasitic disease caused by tapeworms from the genus Taenia, and infection with the larvae form of Taenia is called Cysticercosis. Some species of Taenia are zoonotic, and humans serve as the definitive host, the intermediate host or both. Humans are the definitive hosts for Taenia solium, T. saginata and T. asiatica, however, humans also act as an intermediate host for T. solium and T. asiatica. Animals, such as pigs, are the intermediate host for T. solium and T. asiatica, and cattle are the intermediate host for T. saginata. Humans can be infected by taeniasis when they eat beef or pork that contains larvae (cysticercus). While, cysticercosis is transmitted via food or water contaminated with the eggs of Taenia spp. The transmission may also occur by autoinfection due to lack of hygiene. The diagnosis of taeniasis based on finding the eggs or proglotid in the human feces. For diagnosing cysticercosis in live animals can be done by tongue palpation to find the presence of cysts or nodules. Serological test may also help for diagnosing cysticercosis in humans or animals. Adult tapeworms in the intestine can be killed by anthelmintic and prevention of taeniasis can be conducted by avoiding raw or undercooked pork (T. solium and T. asiatica) and beef (T. saginata). Besides that, to prevent the infection of T. solium, T. saginata or T. asiatica, pigs or cattle should not be exposed to human feces. Key words: Taeniasis, cysticercosis, zoonotic, pig, cattle